2018
DOI: 10.1093/jee/toy279
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Distribution and Movement of the Invasive Pest Delottococcus aberiae (Hemiptera: Pseudococcidae) Within Citrus Tree: Implications for Its Integrated Management

Abstract: Delottococcus aberiae (De Lotto) (Hemiptera: Pseudococcidae) is the most recent species of mealybug introduced to Spain that is affecting citrus. The feeding behavior of D. aberiae causes severe direct damage to citrus fruits, distorting their shape and/or causing reduction in size. There is no information available regarding its distribution within the citrus trees. The main objective of this study was to describe the seasonal distribution of D. aberiae within citrus trees and its migration patterns on the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…3 Between February and July, it migrates from the canopy to the soil via the trunk. 4 Unlike other mealybugs species occurring in citrus, D. aberiae causes distortion and size reduction of fruit that can reduce yields by ≤80%. 5 Fruit damage occurs in late spring, when D. aberiae feeds on the immature fruit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Between February and July, it migrates from the canopy to the soil via the trunk. 4 Unlike other mealybugs species occurring in citrus, D. aberiae causes distortion and size reduction of fruit that can reduce yields by ≤80%. 5 Fruit damage occurs in late spring, when D. aberiae feeds on the immature fruit.…”
Section: Introductionmentioning
confidence: 99%
“…In Mediterranean citrus orchards, D. aberiae completes up to seven generations per year 3 . Between February and July, it migrates from the canopy to the soil via the trunk 4 . Unlike other mealybugs species occurring in citrus, D. aberiae causes distortion and size reduction of fruit that can reduce yields by ≤80% 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other species of citrusinhabiting mealybug, D. aberiae causes severe fruit distortion and size reduction leading to major economic losses (Pérez-Rodríguez et al, 2017). The damaging period ranges from April to July, during the fruit set, when D. aberiae alters fruit cell division while feeding (Martínez-Blay et al, 2018b). Generally, D. aberiae is distributed throughout the entire tree canopy, but aggregate on fruits when they become available, resulting in direct damage (Pérez-Rodríguez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, D. aberiae is distributed throughout the entire tree canopy, but aggregate on fruits when they become available, resulting in direct damage (Pérez-Rodríguez et al, 2017). In the early spring, gravid D. aberiae females descend down the trunk into the soil searching for shelter in the subterranean crown (Franco et al, 2009;Martínez-Blay et al, 2018b). Once in the soil, the females deposit ovisacs, and, upon emergence, nymphs climb again to the upper part of the tree (Martínez-Blay et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…The population trends of D. aberiae in citrus have been recently investigated in Spain by visual examination of plant material, sampling developmental stages in corrugated cardboard band traps and detecting male flights in adapted sticky traps. 7,8 The seasonal trend revealed that D. aberiae density increases in spring, and reaches its first significant maximum in May and June, to coincide with fruit development in the Mediterranean Region, before developing on fruits until the end of August, and then decreasing and remaining at low levels for the rest of the year. 7 In that work, visual examinations and samplings of developmental stages revealed several overlapping generations (two to four).…”
Section: Introductionmentioning
confidence: 99%